Remaja Mesjid Melek Digital: Menangkal Konten Deepfake di Media Sosial - Yuly Rahmi Pratiwi; Amelia Fitri; Roiyatul Ruqayah (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2026)
The rapid development of Artificial Intelligence (AI) technology has introduced new threats such as deepfakes, which can realistically manipulate video and audio. Teenagers, being the most active internet users, often get caught in the phenomenon of epistemic uncertainty due to an inability to distinguish between authentic and fabricated content. This community service activity aims to enhance critical digital literacy among the youth of Az-Zikra Mosque, Pasir Pengaraian, to effectively counter AI-based cyber threats. The method employed was an interactive and participatory educational seminar, including simulations and practical training for detecting the physical characteristics of deepfakes. The results showed significant success, with an average knowledge surge of 45% among participants. Participants are now able to verify information independently by recognizing visual anomalies such as unsynchronized lip movements, strange blinking patterns, and unnatural skin lighting. In conclusion, strengthening digital literacy capacity through case-based approaches has proven effective in shifting the youth's paradigm from merely consuming media for entertainment to becoming wise and vigilant users. This activity is essential for maintaining a healthy digital ecosystem and protecting the next generation from the misuse of manipulative technology.